The Effect of Training and Employee Development on Work Effectiveness at PT Sriana Putra Group - Fahmi Rifaldi; Editya Nurdiana (Greenation Research & Yayasan Global Resarch National, 2026)
The rice milling industry faces competitive challenges that require human resources to work effectively and adaptively. This study aims to examine the effect of training and employee development on work effectiveness at PT Sriana Putra Group. The research employed a quantitative approach with a causal design. The sample consisted of 120 production employees selected using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that training and development have a positive and significant effect on work effectiveness, both individually and simultaneously. The regression model explains 68% of the variance in work effectiveness, with training and development coefficients of 0.287 and 0.315, respectively. These findings highlight the importance of integrating technical training and career development to improve operational performance. The study contributes to human resource management practices in the rice milling sector and reinforces the concept of competency development as a strategy for enhancing work effectiveness in production systems.